If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 3y = 24 + 1y Solving 6x + 3y = 24 + 1y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. 6x + 3y + -3y = 24 + 1y + -3y Combine like terms: 3y + -3y = 0 6x + 0 = 24 + 1y + -3y 6x = 24 + 1y + -3y Combine like terms: 1y + -3y = -2y 6x = 24 + -2y Divide each side by '6'. x = 4 + -0.3333333333y Simplifying x = 4 + -0.3333333333y
| 5x-2(-8)=6 | | 6=u+9 | | 2a+18=5a+6 | | 7(7x-9)=67x+7v*8x | | 2x+2y+1+6y+x-6=180 | | 1/3x=-2/5 | | x+5x=336 | | 7/3+6x=2/3-7x | | 8x+16y+z=400 | | 4/e^3x | | 1.0047*8.2= | | 2(x+4)=3(2x-4) | | 2sin^2x=5cos^2x-3 | | Y=-.025x^2+x+6 | | x+2=2x+8 | | 4y+1=1 | | 4sin^2(2x)-2=0 | | 2ln(x+3)-3=0 | | 3x+2=-7+6x | | -4x-8x=-5-103 | | sec^2=2tan | | x+8x=-7+34 | | 5c+2=2c-7 | | 44=-6x+8 | | 5x-7x=3-5 | | -4x-2=23 | | -31=8x-(2x-5) | | 3(8x+16)-12=2+(7-3x) | | 4x^2-8x^2-96=0 | | 54(x^2+3)=0 | | (-7x/3)-1=-1-(7x/8) | | 35=x+(2x-1)+(2+14x) |